The Effect of Digital Supply Chain, Delivery Performance, and Product Availability on Customer Satisfaction with Risk Mitigation as a Mediating Variable at PT Simpur Mobil Lampung - Nur Asiah; Lestari Wuryanti; Ayu Nursari (International Journal of Management, Economic and Accounting, 2026)
This study aims to analyze the influence of Digital Supply Chain, Delivery Performance, and Product Availability on Customer Satisfaction with Risk Mitigation as a mediating variable in PT Simpur Mobil Lampung. The research uses a quantitative approach with a survey method through the distribution of questionnaires to 172 respondents of workshop customers who are partners of the company. Data were analyzed using multiple linear regression and mediation tests with the help of IBM SPSS software. The results of the study show that Digital Supply Chain, Delivery Performance, and Product Availability have a positive and significant effect on Customer Satisfaction partially or simultaneously. Risk Mitigation has been proven to have a positive and significant effect on Customer Satisfaction, as well as mediating the relationship between Delivery Performance and Customer Satisfaction, but does not mediate the relationship between Digital Supply Chain and Product Availability to Customer Satisfaction. The Adjusted R Square value of 0.472 indicates that the research model is able to explain 47.2% of the variation in Customer Satisfaction, while the rest is influenced by other factors outside the research model. These findings indicate that improved digital integration, delivery performance, product availability, and effective risk management are important factors in improving customer satisfaction in automotive distribution companies.